Genomic diversity and evolution of quasispecies in Newcastle disease virus infections - Jadhav, A; Zhao, L; Liu, W; Ding, C; Nair, V; Ramos-Onsins, SE; Ferretti, L (MDPI, 2020)
Newcastle disease virus (NDV) infections are well known to harbour quasispecies, due to the error-prone nature of the RNA polymerase. Quasispecies variants in the fusion cleavage site of the virus are known to significantly change its virulence. However, little is known about the genomic patterns of diversity and selection in NDV viral swarms. We analyse deep sequencing data from in vitro and in vivo NDV infections to uncover the genomic patterns of diversity and the signatures of selection within NDV swarms. Variants in viruses from in vitro samples are mostly localised in non-coding regions and 3′ and 5′ untranslated regions (3′UTRs or 5′UTRs), while in vivo samples contain an order of magnitude more variants. We find different patterns of genomic divergence and diversity among NDV genotypes, as well as differences in the genomic distribution of intra-host variants among in vitro and in vivo infections of the same strain. The frequency spectrum shows clear signatures of intra-host purifying selection in vivo on the matrix protein (M) coding gene and positive or diversifying selection on nucleocapsid (NP) and haemagglutinin-neuraminidase (HN). The comparison between within-host polymorphisms and phylogenetic divergence reveals complex patterns of selective pressure on the NDV genome at between- and within-host level. The M sequence is strongly constrained both between and within hosts, fusion protein (F) coding gene is under intra-host positive selection, and NP and HN show contrasting patterns: HN RNA sequence is positively selected between hosts while its protein sequence is positively selected within hosts, and NP is under intra-host positive selection at the RNA level and negative selection at the protein level.